PERBANTUAN SATUAN POLISI PAMONG PRAJA DALAM EKSEKUSI TANAH NEGARA YANG DIKUASAI WARGA: Munir Wadi - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2017)
The authority of the Civil Service Police Unit to control and ensure the execution of these duties is orderly and conducive, for its implementation it is necessary repressive action to be able to discipline if there are other parties that apply to it. A civil service police unit whose authorities are almost identical to that of the Police as a centralized apparatus in cases of execution and other cases. If more functions and roles of the Civil Service Police Unit, especially in the act of execution of land, different roles are different from the functions that exist in the Legislation function and the role of Satuan Pamong Praja Police Unit is needed by the community in creating a sense of spirit and order for community life itself Based on the Local Regulation. The countries controlled by the Civil Service Police Unit shall be assisted in the exercise of authority for the first time through the decree of the Governor and the second on the assistance of the execution of the decisions made on the instruction of the execution order delivered to the head of the Kota Pamong Praja City Police Unit.